An autopsy case of fatal acute peritonitis complicated by illegal acupuncture therapy. (July 2017) - Kim, DongJa; Lee, SangHan
Highlights: Fatal acute peritonitis caused by acupuncture is very rare complication. The majority of infections are caused by bacterium. Sterile technique and anatomical knowledge are essential in acupuncture therapy. Abstract: Acupuncture is an alternative medical therapy and widely practiced in Northeast Asia. Although it is known as a safe procedure, complications including infection, pneumothorax, hemorrhage, and cardiac tamponade have been reported. The authors present a rare case of fatal acute peritonitis due to penetration of acupuncture needles directly into the abdominal and pelvic cavity. The victim was a 55-year-old woman who had a recent history of chemo-radiotherapy due to breast cancer. She was collapsed three days after receiving acupuncture. She had symptoms of fever and chilling sensation, general myalgia, and vomiting during three days. The autopsy revealed several needle marks in the lower abdomen and 180 ml of bloody exudate in the abdominal cavity. There was no visible intestinal perforation, but hemorrhagic foci in the mesentery and paracolic area of sigmoid colon were noted. The deepest portion was 13.5 cm from the needle marks on the abdominal skin. The practitioner had not a Chinese medical license. He was accused of illegal medical practice and manslaughter. Acute peritonitis associated with acupuncture might be caused by inadequate sterilization of skin and needle itself and/or direct mesentery injury.